KARAKTERISTIK PASIEN DENGAN CATHETER URINARY TRACT INFECTIONS (CAUTI) - Wardah Fauziah; Novian Mahayu Adiutama; Fhandy Aldy Mandhatyi (Poltekkes Kemenkes Aceh, 2022)
Urinary tract infections may increase the prevalence of healthcare-associated infections, which reaches 40%. Catheter-Associated Urinary Tract Infections (CAUTI) is the most common urinary tract which occurs in patients.. This study aims to find out the identifications of the Catheter Urinary Tract Infections (CAUTI) based on characteristics in Subang Regency Regional Hospital. This study is a descriptive study, based on primary and secondary data. The population in this study was all patient on diagnostic CAUTI at the Intensive Care Unit Subang District Hospital. The results of this study found that there are patient with CAUTI The results of the analysis showed that the average age of respondents in the control group was 48.42 years, with the youngest age being 18 years and the oldest being 60 years (standard deviation 10.67). Based on the statistical results showed that most of the respondents were male, namely 41 people (62.12%) and 25 people (37.88%).